ALGORITHMS FOR SELECTING THE OPERATING MODE OF THE TECHNOLOGICAL PROCESS OF WAVEGUIDE PATHS INDUCTION BRAZING - Tynchenko, Vadim; Anton, Milov; Kukartsev, Vladislav; Bukhtoyarov, Vladimir; Tynchenko, Valeriya; Bashmur, Kirill (Journal of Applied Engineering Science, 2021)
The article presents the development of a method for selecting the operating mode of the induction brazing process based on intelligent methods. The use of intelligent methods is due to the presence of uncertain conditions caused by the complexity of the initial setting of the technological parameters of the induction brazing process, the error of measuring instruments, and the human factor. The use of smart methods will make it possible to reduce the impact of negative factors, remove uncertainty, and adequately perform the initial set of technological parameters for the induction brazing process. Artificial neural networks, the fuzzy controller and the neural fuzzy controller have been chosen as the smart methods in this work. The article gives a brief overview of the above methods, provides a rationale for the choice of intelligent methods, and also compares their effectiveness. Based on the results of the experimental efficiency check, the most suitable method for determining the choice of induction brazing process operation is proposed.
Keywords: neural networks, fuzzy controller, neuro-fuzzy controller, automated control system, induction brazing, waveguide paths, intellectual system